Direct lysine dimethylation of IRF3 by the methyltransferase SMYD3 attenuates antiviral innate immunity - Zixuan Wang; Xiaoyun Chen; Chunchun Zhu; Sijia Fan; Jinhua Tang; Hongyan Deng; Xueyi Sun; Xing Liu; Wuhan Xiao (Proceedings of the National Academy of Sciences, 2025)
Interferon regulatory factor 3 (IRF3) is the key transcription factor in the type I IFN signaling pathway, whose activation is regulated by multiple posttranslational modifications. Here, we identify SMYD3, a lysine methyltransferase, as a negative regulator of IRF3. SMYD3 interacts with IRF3 and catalyzes the dimethylation of IRF3 at lysine 39. This modification reduces IRF3 phosphorylation, dimerization, and subsequent nuclear translocation, leading to the inhibition of downstream type I interferon production. In addition, Smyd3 -deficient mice are more resistant to RNA and DNA viral infections. Zebrafish lacking smyd3 or treated with the inhibitor BCI121 are also more resistant to viral infection. Our findings reveal a role for SMYD3 in the regulation of antiviral innate immunity and provide insight into a specific modulation of IRF3 that affects its activation.